Peningkatan Resiliensi Care Giver Melalui Pemberdayaan Keluarga Sehat Jiwa di Wilayah Kerja Puskesmas Kota Padang - Susanti, Amelia; Arianti, Diana (Universitas Alifah Padang, 2024)
Schizophrenia causes personality changes and severe social maladjustment so that schizophrenic sufferers experience personal, social, vocational and physical maladjustment. This makes schizophrenic sufferers dependent on other people, especially family members as caregivers. Families who have family members with schizophrenia need strong resilience. Family resilience will be achieved if it gets positive support from the surrounding environment. One of the supports from the surrounding area is the formation of groups that voluntarily want to help families and their environment with mental health problems. One effort that can be made is by providing health education and providing training to community groups around the client's residence. The aim of this activity is to increase caregiver resilience in caring for family members who experience schizophrenia. This service activity takes the form of increasing family knowledge by empowering care givers to increase resilience in order to achieve mentally healthy families through the formation of a mentally healthy family group of 30 people in Andalas Village, the working area of ??the Padang City Health Center. The results of the activity showed an increase in family resilience in caring for family members with schizophrenia. It is hoped that after this activity, family knowledge and empowerment will increase so that mental health problems can be minimized